Biodegradable Cationic and Ionizable Cationic Lipids: A Roadmap for Safer Pharmaceutical Excipients. Issue 17 (6th January 2023) - Jörgensen, Arne Matteo; Wibel, Richard; Bernkop‐Schnürch, Andreas
Abstract: Cationic and ionizable cationic lipids are broadly applied as auxiliary agents, but their use is associated with adverse effects. If these excipients are rapidly degraded to endogenously occurring metabolites such as amino acids and fatty acids, their toxic potential can be minimized. So far, synthesized and evaluated biodegradable cationic and ionizable cationic lipids already showed promising results in terms of functionality and safety. Within this review, an overview about the different types of such biodegradable lipids, the available building blocks, their synthesis and cleavage by endogenous enzymes is provided. Moreover, the relationship between the structure of the lipids and their toxicity is described. Their application in drug delivery systems is critically discussed and placed in context with the lead compounds used in mRNA vaccines. Moreover, their use as preservatives is reviewed, guidance for their design is provided, and an outlook on future developments is given. Abstract : Cationic and ionizable cationic lipids are widely used for pharmaceutical formulations. However, their toxicity is seemingly limiting their applicability. Formation of biodegradable cationic lipids overcomes adverse effects while maintaining functionality. The use of natural building blocks provides degradation into safe metabolites. Moreover, endogenous building blocks may improve their efficacy as complexing agents and preservatives.